Hasil Belajar Matematika Siswa Ditinjau dari Interaksi Tes Formatif Uraian dan Kecerdasan Emosional - Supardi U. S. Supardi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
This study aims to analyze the results of learning mathematics in terms of the effect of the interaction between description and formative tests students' emotional intelligence. Research using experimental methods to design a 2x2 factorial treatment by level, and get the results as follows: (1) Overall, the results of the students' mathematics learning structured descriptions given formative tests is higher than that given in descriptions of formative tests are free. (2) There is an interaction effect descriptions and formative tests of emotional intelligence to the results of students' mathematics learning. In the group of students who are given the description of structured formative test results obtained studying mathematics students who have low emotional intelligence is higher than the students who have high emotional intelligence, while in the group of students were given a description of formative tests obtained free math learning outcomes of students who have low emotional intelligence no different from students who have high emotional intelligence. In order to improve the quality of mathematics learning, teachers should be able to conduct a formative test innovation in narrative form. Giving the description formative tests should be tailored to the level of emotional intelligence of students.